2006
DOI: 10.1373/clinchem.2006.071456
|View full text |Cite
|
Sign up to set email alerts
|

Unfavorable Prognostic Value of Human Kallikrein 7 Quantified by ELISA in Ovarian Cancer Cytosols

Abstract: Background: Human tissue kallikrein 7 (gene, KLK7; protein, hK7) is a member of the kallikrein family of secreted serine proteases. Reports indicate that in ovarian cancer, KLK7 is significantly up-regulated at the mRNA level. The aim of this study was to determine whether hK7, measured quantitatively by ELISA in ovarian cancer cytosols, is a prognostic biomarker for ovarian cancer. Methods: We used a newly developed ELISA with 2 monoclonal antibodies to quantify hK7 production in 260 ovarian tumor cytosols an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 29 publications
3
35
3
Order By: Relevance
“…Our work (Supplementary Fig. S4; Supplementary Table S3) confirmed that increased KLK7 expression is a hallmark (15) of EOC, particularly the serous subtype and an association between high KLK7 levels with high tumor grade, chemoresistance, and shorter survival time (16)(17)(18). We showed that KLK7 directs MCA formation and chemoresistance likely by upregulating α 5 β 1 integrin pathways.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Our work (Supplementary Fig. S4; Supplementary Table S3) confirmed that increased KLK7 expression is a hallmark (15) of EOC, particularly the serous subtype and an association between high KLK7 levels with high tumor grade, chemoresistance, and shorter survival time (16)(17)(18). We showed that KLK7 directs MCA formation and chemoresistance likely by upregulating α 5 β 1 integrin pathways.…”
Section: Discussionsupporting
confidence: 76%
“…Our clinical data (Supplementary Fig. S4; Supplementary Tables S1 and S3) and a previous report showed that patients who had shorter progression-free and overall survival time after surgery had increased KLK7 expression (18). We then investigated if KLK7-expressing cells proliferate faster and how they respond to chemoreagents.…”
Section: Klk7 and α5/β1 Integrins Are Coexpressed In Serous Primary Ementioning
confidence: 91%
See 1 more Smart Citation
“…For example, the following kallikreins (transcripts or proteins) are overexpressed in cancerous tissues, in comparison with normal or benign ovarian tissues, and to correlate with higher stage and grade and poor survival (in general, unfavorable prognosis) in ovarian cancer: KLK4 (20 -23), KLK5 (10, 24 -28), KLK6 (29 -39), KLK7 (5, 27, 35, 40 -42), KLK10 (26, 31, 35 -39, 43 -48), KLK11 (26,49), and KLK15 (50). On the other hand, another group of kallikreins was also found to be overexpressed in ovarian cancer but this overexpression correlated with lower stage and grade and increased patient survival (favorable prognosis) as follows: KLK8 (26,35,51), KLK9 (52), KLK11 (35,36), KLK13 (26,53), and KLK14 (40).…”
Section: Discussionmentioning
confidence: 99%
“…(8) Both KLK5 and KLK7 were reported to be overexpressed in several cancers, including ovarian, (9)(10)(11)(12)(13)(14) lung,…”
mentioning
confidence: 99%